TRAILER STEERING WHEEL KINEMATICS (Perner's Contacts, 2024)
This paper addresses the issue of a road vehicle passing around a curve. The text discusses the kinematics of negotiating a curve for road vehicles, particularly for a vehicle combination. I chose a truck tractor and trailer as the vehicle combination. In a conventional combination, the wheel tracks of the tractor and the trailer wheels are different when going around a curve. This makes the path (lane width) bigger. This situation is very limiting when manoeuvring the vehicle in confined spaces, such as city streets and minor roads. Therefore, in the paper I have dealt with a mathematical definition for the trailer wheel angle. The outcome of this paper is a mathematical model offering a definition of the partial angles of rotation of the trailer axles so that these wheels follow the path of the tractor. This will significantly improve the maneuverability of the vehicle. I also foresee a great benefit in the autonomous driving of a vehicle combination. It is fully sufficient for the trailer to have fewer sensors mapping the vehicle’s surroundings without compromising the high level of safety.
Keywords: trailer; steering; vehicle stability